The Ombudsman Concept and Human Rights Protection - Satyanand, Anand (Victoria University of Wellington Law Review, 1999)
"This article traces development of the modern Ombudsman concept, internationally and in New Zealand, that originates from the Scandinavian state model which calls upon Ombudsmen to investigate allegations of government maladministration. It secondly notes, in a similar fashion, the broad themes of development of human rights protection and the movement from international multipartite resolutions to individual enactment and practice in states like New Zealand. Thirdly, there will be some description of the areas in which the Ombudsman concept can be said to make some kind of contribution to the protection of human rights. Lastly, it will observe some differing trends overseas, which may come to apply in this country."